Indigenizing Education: lessons learned, pathways forward - Sammel, Alison; Whatman, Susan; Blue, Levon (Springer, 2020)
Our primary goal for writing this book has been to bring together First Nations’ educators and non-Indigenous educators in Australia and Canada to share their research in a dialogic, practitioner-focused way about what it means to Indigenize education in whichever settings that educational practices occur. In doing so, each author has taken a stand in seeking to imagine and transform educational systems and practices to those that support and celebrate the knowledges and perspectives of Indigenous Peoples. This chapter focuses on revisiting how the contributors have illustrated and responded to the ten themes raised in Chapter 1. In doing so, they offer site-specific, community-led, insights into how other educators might also take up what Tripcony (2004) called “everybody’s business” in Indigenizing education No Full Text